Temporal and spatial environmental structure of the Humacao Natural Reserve lagoon system, Puerto Rico - Ferrer, Orlando; Dibble, Eric; Jackson, Donald; Rundle, Kirk (Ciencia, 2011)
In this paper we examined the temporal and spatial environmental structure of the lagoon system at Humacao Natural Reserve (HNR), Puerto Rico under a restricted, imposed water-flow regime to determine if: 1) the lagoon system maintained its estuarine conditions, 2) there were defined environmental gradients along the longitudinal distribution of the lagoons, and 3) there were hypo- or hyperhaline conditions in the lagoon system. We collected environmental data as part of a broad project effort to evaluate the fisheries of the HNR. Data were analyzed with analysis of variance using mixed linear models and principal components analysis. Two sub-systems environmentally different were identified in the HNR lagoon system: Mandri System (Mandri 1, 2, and 3 lagoons), and Santa Teresa System (Santa Teresa 1 and 2 lagoons). The lagoon system at HNR kept its estuarine conditions under low levels of precipitation and long-term isolation from the sea. There was a salinity gradient; salinity decreased as we moved along the linear series of lagoons from Mandri 1 to Santa Teresa 2. The environmental structure of the lagoons changed as a consequence of the interplaying effect of precipitation and evaporation; either hypo- or hyperhaline conditions that could eventually limit fish and invertebrate communities were not directly measured in the HNR lagoon system. Dissolved oxygen was sufficiently high to support even those species most sensitive to hypoxia; we never recorded hypoxia ( < 2 mg/L of dissolved oxygen). Under the prevailing exceptional environmental conditions, the HNR lagoon system offered sufficient spatiotemporal structure to fish and invertebrate populations to develop.